The Assessment of Perceived Risk of Chemical-related Illness Among Inhabitant Community Adjacent to an Industrial Unit - Maryam Negar Saberiyan Sani; Rahman Akbari (International Journal of New Chemistry, 2019)
The perceived risk is assessed in order to conduct subjective evaluation of individual or community of probability of occurrence of accidents, crashes, and way of exposure to the related consequences. Although such estimation may not comply with what it occurs in real situation since this part is totally related to psychological aspect and at the same time it should be incorporated in planning for risk management. With respect to literacy, cultural, and gender levels and beliefs in communities, perception of the probable risk may be followed by some fluctuations. It has been tried in the present project to explore effect of factor of fear of disease on perceived possible risk among the people who live at neighborhood of MDF Manufacturing Companies. To analyze the rate of effect of fear of disease on the perceived possible risk at region and their relationship with demographic attributes including age, gender, education, having children, and employment in factory, the questionnaire with close-end questions of Likert spectrum type was administered. Data were analyzed by SPSS (v.16) and two-sample t-test and Pearson’s correlation coefficient and linear regression with (p